The Relationship Between Vitamin D and Postoperative Atrial Fibrillation: A Prospective Cohort Study - Ohlrogge, Amelie H.; Brederecke, Jan; Ojeda, Francisco M.; Pecha, Simon; Börschel, Christin S.; Conradi, Lenard; Rimkus, Vanessa; Blankenberg, Stefan; Zeller, Tanja; Schnabel, Renate B. (Frontiers in Nutrition, 2022)
Background and Aims The relationship between postoperative atrial fibrillation (POAF) and 25-hydroxyvitamin D [25(OH)D] concentration as well as vitamin D supplementation has been discussed controversially. The relation of pre-operative vitamin D status and POAF remains unclear. Methods and Results We analysed the risk of POAF in a prospective, observational cohort study of n = 201 patients undergoing coronary artery bypass graft surgery (CABG) with 25(OH)D concentration. The median age was 66.6 years, 15.4% were women. The median (25th/75th percentile) vitamin D concentration at baseline was 17.7 (12.6/23.7) ng/ml. During follow-up we observed 48 cases of POAF. In age, sex, and creatinine-adjusted analyses, 25(OH)D was associated with an increased risk of POAF, though with borderline statistical significance [odds ratio (OR) 1.85, 95% confidence interval (CI) 0.87–3.92, p-value 0.107], in further risk factor-adjusted analyses the results remained stable (OR 1.99, 95% CI 0.90–4.39, p-value 0.087). The subgroup with vitamin D supplementation at baseline showed an increased risk of POAF (OR 5.03, 95% CI 1.13–22.33, p-value 0.034). Conclusion In our contemporary mid-European cohort, higher 25(OH)D concentration did not show a benefit for POAF in CABG patients and may even be harmful, though with borderline statistical significance. Our data are in line with a recent randomised study in community-based adults and call for further research to determine both, the clinical impact of elevated 25(OH)D concentration and vitamin D supplementation as well as the possible underlying pathophysiological mechanisms.